-2x+9=-3x+29

Simple and best practice solution for -2x+9=-3x+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+9=-3x+29 equation:


-2x+9=-3x+29

We simplify the equation to the form, which is simple to understand
-2x+9=-3x+29

We move all terms containing x to the left and all other terms to the right.
-2x+3x=+29-9

We simplify left and right side of the equation.
+1x=+20

We divide both sides of the equation by 1 to get x.
x=20

See similar equations:

| 7x-16=6x-12 | | Z=5+2i | | -4(x-2)=4(2x+5) | | -log*(x)=0.85 | | 20x+25=19x+29 | | a(1+2a)-a(4a-5)= | | 25x^4=61x^2-36 | | 12(h-1)=6h+4+2 | | -2m+0=180(-49y) | | 198=x+2*x*2 | | 14+5(2x+2)=-5 | | 8+3x+4=10 | | 198=x+2+x+2 | | 7-2n-n=-14 | | 12/42=4w/56 | | -2+0=180(-49y) | | w=3ab | | x/8.9=22 | | 2z+8=4z-4 | | 4(2x-5)=-2(7-3x) | | -150h=400 | | 4x-1=2x-1+x+2 | | 198=l*w*h | | 4x-50=3x+50 | | 0=-16t^2+30t+5 | | 5x-22+8x+46=180 | | t+9-8=5 | | 7x-6=6x-15 | | -5(-12+3x)=-45 | | 36+x^2=-12 | | 40-3b=-b+6(3-4b) | | -2x^2-x-1=0 |

Equations solver categories